Simplified Model Predictive for Controlling Circulating and Output Currents of a Modular Multilevel Converter - Abolfazl Sheybanifar; Seyed Masoud Barakati (AUT Journal of Electrical Engineering, 2022)
Model Predictive Control (MPC) has attracted wide attention recently, especially in electrical power converters. MPC advantages include straightforward implementation, fast dynamic response, simple system design, and easy handling of multiple objectives. In conventional MPC, the optimal value of the cost function is obtained after calculating all switching states, which makes this method impossible to implement. In this paper, a Simplified Model Predictive Control (S-MPC) is presented to control the circulating and output currents in a Modular Multilevel Converter (MMC). Using a discrete mathematical model of MMC and the neighboring index values with respect to their previously applied values, the calculation burden can be reduced rapidly, and even the number of Sub-Modules (SMs) increases. The conventional MPC is expressed for comparison with the proposed method. In addition, a bilinear mathematical model of the MMC is derived and discretized to predict the states of the MMC for one step ahead. A sorting algorithm is used to retain the balancing capacitor voltage in each SM, while the cost function guarantees the regulation of the output current, and MMC circulating current. In the simulation section, the proposed method is implemented in a three-phase MMC with four SMs in each arm. The accuracy and performance of the proposed method are evaluated with simulation and experimental results.